A-184 Comparison of Performance on the Virtual Environment Grocery Store and the CVLT-II. (28th August 2020) - S, Shorter; A, Coldiron; C, Reed; T, Glover; R, Gutierrez; J, Moore; T, Parsons; M, Barnett
Abstract: Objective: The Virtual Environment Grocery Store (VEGS) was created to measure memory and everyday functional abilities (Parsons & McMahan, 2017). The objective of this study was to compare young adults' recall of the VEGS shopping list with the CVLT-II in order to investigate what impact the virtual environment has on recall. Methods: Young adults (ages 18–26, M = 18.90, SD = 1.60; N = 39) completed the VEGS and the CVLT-II. Results: Young adults had higher recall on the CVLT-II than VEGS for immediate recall and delayed free recall, but there were no differences on delayed cued recall and delayed recognition. Conclusion: Immediate and delayed free recall on the VEGS may be more difficult on the VEGS than the CVLT-II, perhaps reflecting the word length effect. The virtual environment may have allowed for deeper levels of processing, explaining the lack of differences on delayed cued recall and delayed recognition.